G02 Decision-making in predictive testing in huntington's disease. (September 2018) - Terenzi, Federica; Ferrari, Camilla; Bartolozzi, Claudio; Rotella, Francesco; Ghelli, Elena; Mascherini, Eleonora; Volpi, Eleonora; Latorraca, Stefania; Bagnoli, Silvia; Nacmias, Benedetta; Piacentini, Silvia; Sorbi, Sandro
Abstract : Objective: The protocol for genetic test in at-risk individuals for Huntington Disease provides a neurological examination and a psychiatric evaluation before to begin the psychological counseling, that provides to engage the client in at least two or more psychological session aimed to support the decision-making process. The present study investigated the at-risk subjects' decision to engage psychological counselling and to carry out genetic test. Materials: The collected data were obtained through the recruitment of people with HD and their families within the European Huntington's Disease Network (EHDN). Using the EHDN Registry, data on clinical signs and symptoms of HD are collected together with the family history of the disease and the data obtained by neurocognitive tests and self-report questionnaires. Methods: One hundred and three individuals at risk for Huntington Disease have been included in the study, obtained from clinical data collected from 2007 and 2017 at the HD Center in Careggi Teaching Hospital. Data were manually retrieved from clinical records and included in a database for analyses. Results: Forty-four (42.7%) subjects, out of 103 at-risk individuals, decided to start the protocol and engaged on psychological counselling about decision making for genetic test. Thirty-one (70.4%) subjects, out of 44 subjects who undertook the protocol, decided to carry out genetic test, while thirteen (30.6%) subjects decided to temporarily stop the psychological counselling. Within our sample, 18 females (58%) have undergone genetic test, among them 13 (72, 2%) were in reproductive period (average age of 29, 4 years). Discussion: The study examined changes in decision-making for and against the predictive genetic test for Huntington's disease during psychological counselling. Our data highlight that a high proportion of subjects changed the initial decision of having the genetic test after psychological counselling, preferring uncertainty to the chance of a negative result.